2023
DOI: 10.1088/1755-1315/1213/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Application Increases the Amount of Nitrogen, Phosphorus and Potassium in the Soil: a Review

Abstract: Biostimulants can be given to seeds, plants, and soil to encourage growth. Improved tolerance to abiotic stressors and higher seed and grain yields and quality results from these components altering critical and biochemical processes throughout plant development. The need for fertilizers can also be minimized because of biostimulants. Biochar is a biostimulant, a porous material with a high sorption capacity, which can be put directly into the soil with fertilizers. Biostimulants can be either naturally occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…The impact of nutrient management on soil health extends to the water-holding capacity of the soil. Numerous inorganic nutrients, including zinc (Zn), nitrogen (N), phosphorus (P), potassium (K), and selenium (Se), have been documented as potential mitigators of drought-induced stress [68] . [69,43] documented that the application of silicon through foliar and soil methods enhances the drought tolerance of potatoes.…”
Section: Strategies For Reducing the Impact Of Droughtmentioning
confidence: 99%
“…The impact of nutrient management on soil health extends to the water-holding capacity of the soil. Numerous inorganic nutrients, including zinc (Zn), nitrogen (N), phosphorus (P), potassium (K), and selenium (Se), have been documented as potential mitigators of drought-induced stress [68] . [69,43] documented that the application of silicon through foliar and soil methods enhances the drought tolerance of potatoes.…”
Section: Strategies For Reducing the Impact Of Droughtmentioning
confidence: 99%
“…In addition, humic acids improve soil chemical and physical properties and fertility by increasing cation exchange surfaces [5][6][7]. Humic acids also increase the soil's ability to retain nutrients and increase the soil's ability to exchange cationic ions [8,9]. As well as hydroxides and organic molecules, which can combine to produce complexes that are either soluble or insoluble in water.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to having a positive impact on soil properties by improving soil aeration, which enhances root spread and growth, as well as its role in increasing nutrient availability, as well as increasing various activities of microorganisms and their secretions, which increase trees resistance to drought conditions, organic fertilizers are also often inexpensive and readily available in local markets [6] . Agriculture professionals are well aware of the significance of organic matter and its significant and influential role in vegetative growth characteristics as well as yield and quality of fruits if it is added to soil or sprayed on vegetative systems, which is, it supplies plants with nutrients without harming environment [7,8,9]. Addition of herd manure increases soil humus content, which increases its ability to exchange positive ions (CEC) and increases readiness of elements through ion exchange process [10].…”
Section: Introductionmentioning
confidence: 99%
“…It also helps in absorption of elements and keeps them close to roots and prevents them from washing out. Root growth and absorption of water and nutrients, which improves plant growth and productivity [11], Addition of animal waste to soil and decomposition by soil microorganism's releases CO2 gas, interaction of this gas with water produces carbonic acid, which reduces soil pH with an increase in nutrient availability and increase carbon metabolism efficiency of plant in photosynthesis process [12,13,14].There are many studies and researches that indicated positive effect of herd manure addition on many different vegetative growth characteristics, [9] in a study, that included three levels of herd manure application (10, 20, 30 %) and compared with control treatment in two grape cultivars they found it significantly increased leaves number and leaf area especially at 30 %. And in a study to find out effect of adding herd manure at (3.3 kg) on olive transplants, [15] found that addition had a significant effect on increasing leaves nitrogen, zinc, phosphor and potassium content compared to control treatment.…”
Section: Introductionmentioning
confidence: 99%